Aspiration of dental prosthesis fragment during a seizure: a case report - Figueira, Jéssica Araújo; Tomo, Saygo; de Castro, Tamara Fernandes; Bernabé, Daniel Galera; Miyahara, Glauco Issamu; Biasoli, Éder Ricardo (ARCHIVES OF HEALTH INVESTIGATION, 2021)
The presence of foreign body inside the tissues, via air or digestive is the frequent accident, mainly in children, that led to obit. The diagnosis may be confirmed by radiograph, endoscopy, broncospy and nasofaringoscopy. The clinical case refers to aspiration of dental prosthesis after facial traumatism during convulsive crisis. The gravity and rareness of this fact demonstrates odontologic interest, before this picture, the dentist must do the diagnostic and refer the patient refer the patient primarily to treatment.